Engineering Against Fracture - Pantelakis, Spiros (Springer, 2017)
This volume consists of selected papers from the first conference on Engineering Against Fracture, held in Patras, Greece, May 28-30, 2008. The book delivers a wealth of scientific works aiming to provide solutions to a number of engineering problems found in several industrial sectors including aeronautics, ship building, material fabrication etc. Following the unique conference concept, Engineering Against Fracture represents the interdisciplinary actions needed for conceptualising, establishing, testing and finally solving an engineering problem taking into account all the necessary interactions. This is the new model which drives engineering in the 21st century.